2022
DOI: 10.1002/mds.29173
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning–Based Approach to Discrimination of Tauopathies Using [18F]PM‐PBB3 PET Images

Abstract: A BS TRACT: Background: We recently developed a positron emission tomography (PET) probe, [ 18 F]PM-PBB3, to detect tau lesions in diverse tauopathies, including mixed three-repeat and four-repeat (3R + 4R) tau fibrils in Alzheimer's disease (AD) and 4R tau aggregates in progressive supranuclear palsy (PSP). For wider availability of this technology for clinical settings, biasfree quantitative evaluation of tau images without a priori disease information is needed. Objective: We aimed to establish tau PET path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Florzolotau is a new chemical entity discovered at Institutes for Quantum Life and Medical Science at National Institutes for Quantum Science and Technology, Chiba, Japan. Results from nonclinical and clinical studies so far have shown that florzolotau binds to tau lesions with high affinity and less non-specific off-target binding including MAO-B and MAO-A, and shown the probe captures not only Alzheimer's disease but also non-Alzheimer-type tau pathologies with a dynamic range sufficient for differentiation [13,14], and these findings have been confirmed by other investigators [15]. The binding sites of florzolotau in the β-helix of paired helical and straight filaments of tau from Alzheimer's disease have been reported [16].…”
Section: Introductionmentioning
confidence: 99%
“…Florzolotau is a new chemical entity discovered at Institutes for Quantum Life and Medical Science at National Institutes for Quantum Science and Technology, Chiba, Japan. Results from nonclinical and clinical studies so far have shown that florzolotau binds to tau lesions with high affinity and less non-specific off-target binding including MAO-B and MAO-A, and shown the probe captures not only Alzheimer's disease but also non-Alzheimer-type tau pathologies with a dynamic range sufficient for differentiation [13,14], and these findings have been confirmed by other investigators [15]. The binding sites of florzolotau in the β-helix of paired helical and straight filaments of tau from Alzheimer's disease have been reported [16].…”
Section: Introductionmentioning
confidence: 99%
“…To validate our hypothesis, we collected plasma samples from subjects who underwent PET with both 11 C-Pittsburgh Compound B ( 11 C-PiB) and 18 F-florzorotau (aka PM-PBB3/APN-1607) for the examination of Aβ and tau depositions in the brain, respectively. 34,35 We demonstrated a strong correlation of between plasma levels of p-tau181 fragments measured using our mid-region-directed assay (hereinafter called mid-p-tau181) and tau PET tracer retention but no linear correlation between plasma N-p-tau181 levels and tau PET data, suggesting the clinical usefulness of the novel assay as a surrogate biomarker for PET-visible tau pathologies.…”
Section: Introductionmentioning
confidence: 90%
“…Visual assessment of PI-2620 images in one study provided better differentiation of PSP-RS from healthy controls compared with visual reads of MRI, and an index considering quantitative values from both PI-2620 (globus pallidus uptake) and MRI (Midbrain-to-pons ratio) performed better than the midbrain-to-pons ratio alone in differentiating PSP and controls (AUROC = 0.98 versus 0.93), particularly in clinically less affected patients [20 ▪ ]. A machine learning approach was also utilized to demonstrate that PM-PBB3 could differentiate PSP-RS from Alzheimer's dementia with high sensitivity (87.6%) and specificity (98.6%), with the globus pallidus and medial temporal lobe the most important regions for differentiation [21 ▪ ]. PM-PBB3 can also differentiate PSP-RS from PD and MSA [18].…”
Section: Improving Imaging-based Differential Diagnosismentioning
confidence: 99%